PSI-14 Feeding β-agonists under heat stress conditions in feedlot cattle. (30th November 2020) - Grijalva, Pablo C; Reith, Rachel; Sieck, Renae L; Swanson, Rebecca; Schmidt, Ty B; Petersen, Jessica L; Yates, Dustin T; Garcia, Samuel; Diaz, Duarte
Abstract: Red Angus steers (n = 24; 260 ± 25 kg) were used to analyze the effects of supplementation of zilpaterol hydrochloride (ZH) under heat stress conditions on respiration rate (RR), rectal temperature (RT), growth performance (GP), and carcass traits (CT). Steers were randomly assigned to a 2 x 2 factorial treatment arrangement (n = 6/group) with factors including heat stress (HS; THI=71 to 83) or thermal neutral (TN; THI=27 to 39) conditions and with/without supplementation of ZH (0 or 8.38 mg/kg/d on 88% DM basis). Steers were provided 9 d to acclimate to tie stalls rooms under TN conditions before starting the study. TN steers were pair-fed to the average daily dry matter intake (DMI) of HS steers. Ad libitum water consumption (WC) was recorded daily. HS and TN steers were harvested on d 22 and 23, respectively. By design, DMI was not different between environments (P = 0.43). DMI also did not differ between supplement groups (P = 0.31). RT, RR, and WC were greater (P < 0.01) in HS steers compared to TN steers. There was a supplement by environment interaction (P = 0.02) for RT, as HS steers fed ZH had lower RT than HS control steers (39.1 vs 39.5 ℃). ADG was 20% higher (P = 0.04) in HS steers compared to TN steers. CT did not differ (P = >0.05) due to environment, treatment, or interactions between environment and ZH supplementation. Our results suggest that feedlot steers under our experimental conditions display some sensitivity to HS through GP, RR, and RT, however, this did not translate to an impact on CT. Furthermore, ZH supplementation under HS conditions appears to impact thermoregulatory responses positively, yet this did not impact GP or CT.